2021
DOI: 10.1186/s13722-021-00265-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating traditional practices and social network visualization to prevent substance use: study protocol for a randomized controlled trial among urban Native American emerging adults

Abstract: Background Nonmedical use of prescription opioids (defined as taking opioid medications for hedonic effects or in a manner other than prescribed) and the use of heroin have emerged in recent years as major public health concerns in the United States. Of particular concern is the prevalence of opioid use among emerging adults (ages 18–25), as this is a developmental period of heightened vulnerability and critical social, neurological, and psychological development. Data from 2015 show that Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…In addition, psychosocial treatment programs can provide culturally appropriate meeting places for patients to gather in healing circles and other traditional events. Research from the US also describes the need for holistic and culturally relevant care that is rooted in the local community with its history, traditions and support networks; authors agree that the opioid epidemic must be addressed at both the individual and community levels and address health policy factors that contribute to the opioid epidemic [31,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, psychosocial treatment programs can provide culturally appropriate meeting places for patients to gather in healing circles and other traditional events. Research from the US also describes the need for holistic and culturally relevant care that is rooted in the local community with its history, traditions and support networks; authors agree that the opioid epidemic must be addressed at both the individual and community levels and address health policy factors that contribute to the opioid epidemic [31,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed an online screener, and those who were eligible were contacted by staff from our Survey Research Group and consented to be part of the study. They were then asked to complete a baseline survey and randomized to receive either one virtual workshop or three virtual workshops and a Wellness Circle (D'Amico et al, 2021). Data for this article originate from an online baseline survey and address aims of a supplemental grant focused on understanding the influence of social networks on health behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…AOD use, this could lead to policy change, allowing for provision and reimbursement for these types of services for AI/AN people (Crump et al, 2020;Johnson et al, 2021;Kaholokula et al, 2017). Our current intervention, TACUNA, is being virtually implemented with these participants and specifically focuses on helping them visualize who in their network engages in risk and protective behaviors so that they can determine whether they need to change their social networks in order to make healthy choices for their future (D'Amico et al, 2021;Dickerson et al, 2022). TACUNA also focuses on tradition and culture and ways that they can connect with others in the AI/AN community.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…The main base of our intervention framework is a group MI intervention developed by D'Amico and colleagues that is available online at no cost ( www.groupmiforteens.org/about ) (GMIT; [ 11 , 12 , 32 , 40 ]. A cluster randomized controlled trial ( n = 9528) revealed a school-wide effect where youth in schools receiving the MI intervention were less likely to initiate alcohol use than youth not receiving the MI treatment [ 32 ].…”
Section: Group Motivational Interviewing For Teensmentioning
confidence: 99%
“…Although efforts are striving to prevent the onset of and frequency of substance and tobacco use for Latine youth, more attention is needed for culturally enhancing prevention interventions. For example, although the Group Motivational Interviewing for Teens (GMIT) has effectively reduced youth substance use in diverse communities [ 11 , 12 ], more research is needed to determine its efficacy in reducing tobacco and alternative tobacco products (ATP) use in a culturally relevant fashion among Latine adolescents. This study, therefore, modified GMIT to include a focus on ATPs (GMIT-ATP).…”
mentioning
confidence: 99%